REVITALISASI NILAI-NILAI ISLAM DALAM MEMBANGUN JIWA KEWIRAUSAHAAN - Haris Faulidi Asnawi (At-Taradhi Jurnal Studi Ekonomi, 2012)
Focusing on the building of entrepreneurial spirit, this article emphasises the impor-tance of Islamic values as the basis to create an independent and competitive ummah (communityof believers). It is widely convicted that our society prefer to be civil servants or employees tostarting their own businesses. This and misperception of religious values and teachings are partlyresponsible for the slow development of the entrepreneurship culture. I argue that we need to revitaliseIslamic values in order to build an entrepreneurial spirit that emphasises honesty and trustwor-thiness. Devotions should not be understood as norrowly as they have often been, and mustbecome a main motivation when one starts or runs a business. It is also crucial to teach thatdishonesty and untrustworthiness will only produce short term profits with no long term bless-ings.